2018
DOI: 10.12659/msm.905354
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gray Matter Density, Regional Homogeneity, and Functional Connectivity in Methamphetamine-Associated Psychosis: A Resting-State Functional Magnetic Resonance Imaging (fMRI) Study

Abstract: BackgroundUsing regional homogeneity (ReHo) blood oxygen level-dependent functional MR (BOLD-fMRI), we investigated the structural and functional alterations of brain regions among patients with methamphetamine-associated psychosis (MAP).Material/MethodsThis retrospective study included 17 MAP patients, 16 schizophrenia (SCZ) patients, and 18 healthy controls. Informed consent was obtained from all patients before the clinical assessment, the severity of clinical symptoms was evaluated prior to the fMRI scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 16 publications
(18 reference statements)
1
20
0
Order By: Relevance
“…Then, the signals were regressed out, including the global signal, cerebrospinal fluid signal and white matter signal, and the 24 head motion parameters. Afterward, the images were smoothed with the Gaussian kernel using the full width at half maximum of 6 mm and bandpass temporal filtered (0.01–0.1 Hz) to reduce the low-frequency drift and physiological high-frequency noise, including the breath and heartbeats ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the signals were regressed out, including the global signal, cerebrospinal fluid signal and white matter signal, and the 24 head motion parameters. Afterward, the images were smoothed with the Gaussian kernel using the full width at half maximum of 6 mm and bandpass temporal filtered (0.01–0.1 Hz) to reduce the low-frequency drift and physiological high-frequency noise, including the breath and heartbeats ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…MA abuse was found to be associated with structural and functional alterations of the brain. In a study that used functional magnetic resonance imaging (fMRI), Zhang et al researched the resting-state functional connectivity (RSFC) between seeds [region of interest (ROI)] selected with a higher value of ReHo and the whole-brain voxels and found different RSFC performance when compared with healthy controls (HCs) ( 26 ). Furthermore, in the studies conducted by Kohno et al ( 27 , 28 ), the midbrain and dorsolateral prefrontal cortex were chosen as ROIs, referring to previous research results.…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated that similar gray matter deficits appear to exist within the left perisylvian region of brain in the posterior inferior frontal gyrus and anterior superior temporal gyrus in both MAP and schizophrenia (Aoki et al, 2013). However, a study by Zhang et al, 2018 revealed that functional and structural deficits associated with gray matter MAP significantly differed from those observed in the schizophrenia group. Gray matter deficits unique to MAP, such as those in the orbitofrontal area or the frontopolar BA 10 cortices, have been implicated in contributing to the symptoms of MAP unique to the disorder (Aoki et al, 2013).…”
Section: Imaging Studiesmentioning
confidence: 99%
“…Gray matter deficits unique to MAP, such as those in the orbitofrontal area or the frontopolar BA 10 cortices, have been implicated in contributing to the symptoms of MAP unique to the disorder (Aoki et al, ). Additionally, regional homogeneity was observed to be negatively correlated with positive symptoms in the left orbital interior frontal gyrus in MAP, and regional homogeneity was found to be negatively correlated with negative symptoms in the right superior frontal gyrus in schizophrenia patients (Zhang et al, ).…”
Section: Biological Basis Of Mapmentioning
confidence: 99%
“…Resting-state functional magnetic resonance imaging (RS-fMRI) is a noninvasive technique and has provided new opportunities to explore the changes of the structure and function in the brain (14). The blood oxygen level dependent low-frequency oscillation signal in the RS-fMRI denotes spontaneous activity of neurons (15).…”
Section: Introductionmentioning
confidence: 99%